The sacred value of gold and money in the joint Slavic folk formulas (based on the works of O. O.Potebnya) - Охріменко, Тетяна Володимирівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2018)
The article analyzes the mythological concept of Olexandr Potebnya, a well-known Ukrainian folklorist and ethnographer. Potebnya's works on the mythology and folklore of the Slavs reflect the ancient notions of our ancestors about important common elements of monetary culture. This culture is associated with such symbols as gold, silver and other precious metals, hidden treasures, valuable natural resources, primary elements of being (earth, water, fire, air, thunder), women's origin, heavenly and demonic worlds. Folk, poetic interpretation by the Slavs of the phenomenon of wealth includes the following: human health, fertility of the land, young maiden beauty, fruitfulness and happy fate of the young family, long and fun years of life, welfare in the economy, God's favor, help of ancestors.